EFFICACY OF CALCIUM SUPPLEMENTATION ON GROWTH AND EGG QUALITY IN DESI LAYING HENS (GALLUS GALLUS DOMESTICUS) - ALI, I; AHMAD, M; RASHEED, S; HUSSAIN, A; SAEED, I (Biological and Clinical Sciences Research Journal, 2024)
Abstract This study examined the effects of Ca addition on the growth and egg quality of desi-laying hens. The study was conducted in a village located in District Muzaffargarh, Punjab, Pakistan. A total of 40 desi hens, approximately 8 weeks old, were procured from the local market which were included in the study. These hens were housed in wooden cages under uniform environmental conditions. To ensure a smooth transition, the hens were initially fed a standard diet for 10 days to acclimate them to their new cages and surroundings. Subsequently, a total of four groups (A, B, C, and D) of chickens were made, each group contained ten hens and was assigned to four different diets. These diets were randomly allotted among groups with the inclusion of Ca powder at various levels: 0%, 1%, 1.5%, and 2%. Each group received their respective diet two times daily, at 7:00 AM and 5:00 PM, along with continuous access to clean and fresh water. To assess weight gain, the hens were initially weighed, and thereafter weights were recorded weekly throughout the 42 days of research. The data revealed that the group received the diet with 2% Ca experienced the highest weight gain compared to the control group and the other two treated groups (1071.00g vs. 985.88g vs. 1028.13g vs. 1048.88g) in that order and this variation was significant (P<0.05). For feed efficiency, data on the daily amounts of feed offered refused, and consumed was collected. The results demonstrated that the group fed the 2% Ca diet exhibited better feed efficiency in comparison to the control group and other treatment groups (6.74kg vs. 7.10kg vs. 6.90kg vs. 6.78kg), and this distinction was significant (P<0.10). Likewise, the number of eggs produced and their quality were greater in the hens who received the food containing 2% Ca as compared to the control group and other treatment groups (80 vs. 75.06 vs. 76.625 vs. 78.875) and (10.383mm vs. 0.373mm vs. 0.3mm vs. 0.381mm), correspondingly. Statistics showed that these differences were different (P<0.10). In summary, the results of this study demonstrated that a linear increase in Ca addition in desi laying hens' normal diet, up to a level Of 2%, yielded better performance and to get better production from their laying hens, farmers were advised to add this amount of Ca in the feed of laying hens.